2010
DOI: 10.1016/j.bbamem.2010.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Membrane lysis by gramicidin S visualized in red blood cells and giant vesicles

Abstract: The cationic amphiphilic antimicrobial peptide gramicidin S (GS) is an effective antibiotic. Its applicability is however restricted to topical infections due to its hemolytic activity. In this study, the process of GS induced hemolysis was investigated in detail for the first time. The morphological changes of red blood cells (RBCs) inflicted by GS were visualized and explained in terms of a physical model. The observed fast rupture events were further investigated with giant unilamellar vesicles (GUVs) as mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 41 publications
1
14
0
5
Order By: Relevance
“…Furthermore, experimentally reported bending rigidities vary based on the methods employed [136]. The three main experiments to determine bending rigidities for pure lipid bilayers are diffuse x-ray scattering of flat bilayers [4349], force-based methods to deform a membrane such as the pipette aspiration technique and pulling membrane nanotubes [5058,137144], and fluctuating shape analysis of GUVs [51,59,60,145156]. To measure the rigidity of SUVs and purified synaptic vesicles [64], neutron spin echo (NSE) [6163], and atomic force-microscopy (AFM) experiments have been used [6569].…”
Section: Protein-induced Alterations In Membrane Materials Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, experimentally reported bending rigidities vary based on the methods employed [136]. The three main experiments to determine bending rigidities for pure lipid bilayers are diffuse x-ray scattering of flat bilayers [4349], force-based methods to deform a membrane such as the pipette aspiration technique and pulling membrane nanotubes [5058,137144], and fluctuating shape analysis of GUVs [51,59,60,145156]. To measure the rigidity of SUVs and purified synaptic vesicles [64], neutron spin echo (NSE) [6163], and atomic force-microscopy (AFM) experiments have been used [6569].…”
Section: Protein-induced Alterations In Membrane Materials Propertiesmentioning
confidence: 99%
“…Several studies used this technique to report rigidities of vesicle with added proteins [51,59,156]. In these studies, k c is extracted from thermal fluctuations in the vesicle contours.…”
Section: Protein-induced Alterations In Membrane Materials Propertiesmentioning
confidence: 99%
“…Authors in Ref. suggested that GS did not form discrete, channel‐like stable pores; more likely, GS induces a variety of transient, differently sized defects and fast disintegration of a membrane.…”
Section: Introductionmentioning
confidence: 99%
“…In this theory, an asymmetric plasma membrane is regarded as two protein–lipid layers that are capable of performing a relatively independent adaptive deformation without losing the contact between them. The coupled bilayer theory has frequently been used to interpret the formation of echinocytes and stomatocytes under the action of membrane-active agents, including AMPs [18, 22, 23]. According to this theory, echinocyte formation is conditioned by the accumulation of the actuating agent in the external layer of the membrane.…”
Section: Resultsmentioning
confidence: 99%